Promoting nature conservation by Dutch farmers: a governance perspective†. Issue 3 (4th May 2017) - Runhaar, H. A. C.; Melman, Th. C. P.; Boonstra, F. G.; Erisman, J. W.; Horlings, L. G.; de Snoo, G. R.; Termeer, C. J. A. M.; Wassen, M. J.; Westerink, J.; Arts, B. J. M.
ABSTRACT: Reconciling productive agricultural practices with nature conservation is not only an ecological challenge, but also a demanding matter of governance. This paper analyses the potential as well as the limitations of various governance arrangements, and explores ways to enhance the governance of nature conservation in agricultural landscapes. We assume four conditions to contribute to the performance of these arrangements: farmers should be motivated, demanded, enabled, and legitimized to participate in arrangements that promote nature conservation by farmers. We analyse 10 distinct Dutch governance arrangements in the period 2000–2016, including agri-environment schemes but also privately initiated arrangements. The arrangements target a large but unknown share of farmers and farmlands, but nature conservation ambition levels are generally low to moderate. The expected low-to-moderate performance is associated with a low-to-moderate motivation, demand, and ability. Underlying are stronger forces driving towards intensification and problems farmers face in recuperating the cost of nature conservation. New greening requirements in the EU Common Agricultural Policy and in agri-food supply chains are first, cautious steps addressing these fundamental drivers of ecological degradation. More ambitious greening requirements may contribute to a higher motivation and ability of larger groups of farmers to implement nature conservation measures.